Interclonal Variations in the Molecular Karyotype of Trypanosoma cruzi: Chromosome Rearrangements in a Single Cell-Derived Clone of the G Strain - Lima, Fabio Mitsuo; Souza, Renata Torres; Santori, Fábio Rinaldo; Santos, Michele Fernandes; Cortez, Danielle Rodrigues; Barros, Roberto Moraes; Cano, Maria Isabel [UNESP]; Valadares, Helder Magno Silva; Macedo, Andréa Mara; Mortara, Renato Arruda; da Silveira, José Franco (Public Library of Science (PLoS), 2013)
Trypanosoma cruzi comprises a pool of populations which are genetically diverse in terms of DNA content, growth and infectivity. Inter- and intra-strain karyotype heterogeneities have been reported, suggesting that chromosomal rearrangements occurred during the evolution of this parasite. Clone D11 is a single-cell-derived clone of the T. cruzi G strain selected by the minimal dilution method and by infecting Vero cells with metacyclic trypomastigotes. Here we report that the karyotype of clone D11 differs from that of the G strain in both number and size of chromosomal bands. Large chromosomal rearrangement was observed in the chromosomes carrying the tubulin loci. However, most of the chromosome length polymorphisms were of small amplitude, and the absence of one band in clone D11 in relation to its reference position in the G strain could be correlated to the presence of a novel band migrating above or below this position. Despite the presence of chromosomal polymorphism, large syntenic groups were conserved between the isolates. The appearance of new chromosomal bands in clone D11 could be explained by chromosome fusion followed by a chromosome break or interchromosomal exchange of large DNA segments. Our results also suggest that telomeric regions are involved in this process. The variant represented by clone D11 could have been induced by the stress of the cloning procedure or could, as has been suggested for Leishmania infantum, have emerged from a multiclonal, mosaic parasite population submitted to frequent DNA amplification/deletion events, leading to a 'mosaic' structure with different individuals having differently sized versions of the same chromosomes. If this is the case, the variant represented by clone D11 would be better adapted to survive the stress induced by cloning, which includes intracellular development in the mammalian cell. Karyotype polymorphism could be part of the T. cruzi arsenal for responding to environmental pressure. © 2013 Lima et al.
Keywords: alpha tubulin; beta tubulin; alpha tubulin gene; beta tubulin gene; chromosome band; chromosome breakage; chromosome number; chromosome polymorphism; chromosome rearrangement; chromosome size; clonal variation; controlled study; DNA sequence; epimastigote; gene amplification; gene cluster; gene deletion; gene dosage; gene fusion; gene locus; gene translocation; genetic variability; genome analysis; karyotyping; molecular cloning; nonhuman; nucleotide sequence; parasite isolation; species difference; tandem repeat; telomere; telomere homeostasis; Trypanosoma cruzi